When and Where Do We See Regional Poverty Reduction and Convergence? : Lessons from the Roof of Turkey - Azevedo, Joao Pedro (World Bank, Washington, DC, 2016)
In the past decade, Turkey has experienced a notable level of poverty reduction at all levels (extreme poor, poor, and vulnerable). The steady decline in poverty was also resilient to the decline in gross domestic product per capita growth during the crisis. However, although poverty convergence was strong before the financial crisis, there was an absence of regional convergence afterward. This paper analyzes poverty trends, poverty convergence, economic mobility, and the determinants of poverty reduction at the regional level over the period 2006–13. The analysis finds that agricultural growth in the east was an important contributor to Turkey's regional poverty reduction. In additionally, employment growth in the services sectors boosted poverty reduction throughout the entire country. From a fiscal perspective, the amount of per capita central spending is also linked to poverty reduction, although more strongly for regions in the west.